Contribution of the single photon emission computed tomography with 99mTc red blood cells in splenosis - Muñoz-Bellvis, Luis; Quiñones-Sampedro, Jose E.; Iglesias, Manuel; Blanco, Oscar; Fernandez, Luis Miguel González; Velasco, Carmen Esteban; Sayagués, José María (International Journal of Research in Medical Sciences, 2017)
The term splenosis refers to the presence of auto-transplanted splenic tissue in a heterotopic location. These foci can be localized to the liver simulating a malignant lesion. Sometimes these lesions are difficult to identify using conventional imaging techniques (ultrasound, CT and MR). Then, a scan with denatured erythrocytes marked with 99mTc has proven to be an effective technique to confirm the diagnosis of splenosis and to establish its extension. The incorporation of hybrid imaging techniques (SPECT-CT) into usual clinical practice has increased the precision of the localization of these foci of splenosis. We hereby report the cases of two patients diagnosed with splenosis, the first by laparotomy and the second after performing scintigraphy with red blood cells labeled with 99mTc. In the first case, the laparotomy revealed numerous reticulated nodules on the diaphragmatic peritoneal surface, the transverse colon and the right kidney. Finally, the anatomopathological diagnosis confirmed a case of splenosis. In the second case, the results of the 99mTc marked red blood cell gammagraphy and SPECT-CT were consistent with the diagnosis of splenosis in the patient. To obtain correct information in cases of lesions highly suspicious of splenosis, 99mTc marked red blood cell gammagraphy should be performed due to the high sensitivity and specificity of the test. Combined diagnostic imaging (SPECT-CT), have increased the specificity of this test due to improvements in the characterization of lesions. We believe that the use of this technique will help avoid unnecessary surgical procedures.